2021
DOI: 10.1002/anie.202107855
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of Two Isomers: Enhanced Antiaromaticity/Diradical Character versus Deleterious Ring‐Opening of Benzofuran‐fused s‐Indacenes and Dicyclopenta[b,g]naphthalenes

Abstract: We examine the effects of fusing two benzofurans to s-indacene (indacenodibenzofurans,I DBFs) and dicyclopenta[b,g]naphthalene (indenoindenodibenzofurans, IIDBFs) to control the strong antiaromaticity and diradical character of these core units.S ynthesis via 3-functionalized benzofuran yields syn-IDBF and syn-IIDBF.s yn-IDBF possesses ah igh degree of paratropicity,e xceeding that of the parent hydrocarbon, which in turn results in strong diradical character for syn-IIDBF.I nt he case of the anti-isomers, syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 52 publications
4
23
0
Order By: Relevance
“…Synthesis of extended polyaromatics often provides interesting synthetic challenges that span innovation. In the present case, an attractive synthetic route to diradicaloids is opened by our recent work on radical alkyne periannulations (i.e., “zigzag annulations”) where we developed a new strategy for expanding the scope of π-annulations at the zigzag edge of PAHs (Figure a). Fortuitously, the pericyclizations provide the necessary pieces for accomplishing the synthesis of new diradicals in a concise and modular fashion.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of extended polyaromatics often provides interesting synthetic challenges that span innovation. In the present case, an attractive synthetic route to diradicaloids is opened by our recent work on radical alkyne periannulations (i.e., “zigzag annulations”) where we developed a new strategy for expanding the scope of π-annulations at the zigzag edge of PAHs (Figure a). Fortuitously, the pericyclizations provide the necessary pieces for accomplishing the synthesis of new diradicals in a concise and modular fashion.…”
Section: Resultsmentioning
confidence: 99%
“…HF [a] (%) PG [b] ∆r [c] (Å) ∆Erel (kcal/mol) d H8 [d] (ppm) d H2 [d] (ppm) Some of us recently published a joint experimental and theoretical study of indacenodibenzofurans (IDBFs). [26] We found that syn-IDBF shows a high degree of paratropicity exceeding that of the parent s-indacene, while anti-IDBF exhibits weaker paratropicity. Indeed, experimental 1 H NMR signals for the hydrogens on the central six-membered ring of syn-IDBF are shifted upfield (Hsyn: 5.60 ppm, Figure 2A) compared to those of anti-IDBF (Hanti: 6.15 ppm, Figure 2B).…”
Section: Levelmentioning
confidence: 66%
“…Aromaticity and antiaromaticity are two fundamental physical organic chemistry concepts that underlie several molecular properties of polycyclic conjugated systems. Hence, a widely used approach to design such molecules with novel functions is to tune their electronic structure on the aromatic–nonaromatic–antiaromatic scale. , Apart from structure and reactivity, properties that are influenced by (anti)­aromaticity such as molecular stacking or conductance have recently been the subject of major interest. For example, aromatic systems assemble in a manner to minimize π-orbital repulsion, , while antiaromatic rings are predicted to prefer face-to-face stacking due to the emergence of transannular delocalization. Furthermore, the increment in conductivity within aromatic, nonaromatic, and antiaromatic molecular wires has been rationalized based on their decreasing resistance to redistribute their π-electron systems upon charge transport. As of now, the best approach to probe the effects of (anti)­aromaticity on molecular properties is to design and synthesize new compounds with different conjugation patterns, among which reversible control of (anti)­aromaticity has rarely been reported. ,, …”
Section: Introductionmentioning
confidence: 99%